2018
DOI: 10.1161/circresaha.118.313237
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Vascular Endothelium in Metabolic Homeostasis

Abstract: Our understanding of the role of the vascular endothelium has evolved over the past two decades, with the recognition that it is a dynamically regulated organ and that it plays a nodal role in a variety of physiological and pathological processes. Endothelial cells (ECs) are not only a barrier between the circulation and peripheral tissues, but also actively regulate vascular tone, blood flow and platelet function. Dysregulation of ECs contributes to pathological conditions such as vascular inflammation, ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 230 publications
(222 reference statements)
3
152
2
8
Order By: Relevance
“…Nevertheless, in our patient, we cannot exclude that insulin resistant diabetes could also contribute to endothelial dysfunction, leading to atherosclerosis, as previously suggested in patients with FPLD2 due to LMNA p.Arg482 "hotspot" variants [5]. However, the inverse relationship could also be discussed since it was recently shown that endothelial dysfunction, through secreted factors, may directly alter adipose tissue homeostasis and lead to insulin resistance [54]. Direct evidence that endothelial cell senescence induces adipose tissue metabolic dysfunction and systemic insulin resistance was recently demonstrated in Tie2-TERF2DN-Tg mice, which display an endothelium-specific form of progeria [55].…”
Section: Discussionmentioning
confidence: 63%
“…Nevertheless, in our patient, we cannot exclude that insulin resistant diabetes could also contribute to endothelial dysfunction, leading to atherosclerosis, as previously suggested in patients with FPLD2 due to LMNA p.Arg482 "hotspot" variants [5]. However, the inverse relationship could also be discussed since it was recently shown that endothelial dysfunction, through secreted factors, may directly alter adipose tissue homeostasis and lead to insulin resistance [54]. Direct evidence that endothelial cell senescence induces adipose tissue metabolic dysfunction and systemic insulin resistance was recently demonstrated in Tie2-TERF2DN-Tg mice, which display an endothelium-specific form of progeria [55].…”
Section: Discussionmentioning
confidence: 63%
“…Inflammation is not observed in BMPER iKO mice. Given that vascular inflammation also disrupts function of metabolic tissues such as liver and WAT [18][19][20] , we examined whether BMPER depletion resulted in an inflammatory response in these tissues. In the liver of BMPER iKO and WT mice, the induction of the inflammatory cytokine IL1β ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrosis in the space of Disse is preceded by loss of LSEC differentiation that leads to the defenestration of the LSEC layer and the development of a subendothelial basement membrane: this process is known as capillarization [21,22]. This capillarization associates with the endothelial dysfunction of the LSECs [23,24]. Initially, the defenestration can still be reversed by removing hepatotoxin [25].…”
Section: Endothelial Dysfunction In Liver Fibrosismentioning
confidence: 99%